Regeneration of reptilian scales after wounding: neogenesis, regional difference, and molecular modules. Issue 1 (17th February 2014) - Wu, Ping; Alibardi, Lorenzo; Chuong, Cheng‐Ming
<x xml:space="preserve">Abstract</x> Reptile scale development and regeneration occur through different processes. A–D, embryonic reptile scales develop from a flat bilayer epidermis to symmetric scale anlagen to asymmetric scale anlagen and further to mature scales. E–H, skin regenerates scales from flat wound epidermis to peg formation to elongating pegs and further to differentiating pegs. Despite these differences, they share similarities in proliferation patterns, epithelial–mesenchymal interactions and molecular modules. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>